Different Approaches to Meaning in Primate Gestural and Vocal Communication - Liebal, Katja; Oña, Linda (Frontiers in Psychology, 2018)
In searching for the roots of human language, comparative researchers investigate whether precursors to language are already present in our closest relatives, the nonhuman primates. As the majority of studies into primates’ communication uses a unimodal approach with focus on one signal type only, researchers investigate very different aspects depending on whether they are interested in vocal, gestural, or facial communication. Here, we focus on two signal types and discuss how meaning is created in the gestural (visual, tactile/auditory) as compared to the vocal modality in nonhuman primates, to highlight the different research foci across these modalities. First, we briefly describe the defining features of meaning in human language and introduce some debates concerning meaning in nonhuman communication. Second, with focus on these features, we summarize the current evidence for meaningful communication in gestural as compared to vocal communication and demonstrate that meaning is operationalized very differently by researchers in these two fields. As a result, it is currently not possible to generalize findings across these modalities. Rather than arguing for or against the occurrence of semantic communication in nonhuman primates, we aim at pointing to gaps of knowledge in studying meaning in our closest relatives, and how we might work to close these gaps.